Organizational Aspects of Hemodialysis Care to the Population in Uzbekistan - Jalilova Gulchekhra; Asadov Ravshan (Journal of Coastal Life Medicine, 2023)
The article is devoted to the study of organizational aspects of hemodialysis care for the population of Uzbekistan. The survey was conducted among the heads of medical institutions in all regions of the country, including chief physicians, reserves of main departments, family polyclinics and others.